Maternal high-fructose intake during pregnancy and lactation induces metabolic syndrome in adult offspring - Koo, Soohyeon; Kim, Mina; Cho, Hyun Min; Kim, Inkyeom (Nutrition research and practice, 2021)
Nutritional status and food intake during pregnancy and lactation can affect fetal programming. In the current metabolic syndrome epidemic, high-fructose diets have been strongly implicated. This study investigated the effect of maternal high-fructose intake during pregnancy and lactation on the development of metabolic syndrome in adult offspring. Drinking water with or without 20% fructose was administered to female C57BL/6J mice over the course of their pregnancy and lactation periods. After weaning, pups ate regular chow. Accu-Chek Performa was used to measure glucose levels, and a tail-cuff method was used to examine systolic blood pressure. Animals were sacrificed at 7 months, their livers were excised, and sections were stained with Oil Red O and hematoxylin and eosin (H&E) staining. Kidneys were collected for gene expression analysis using quantitative real-time Polymerase chain reaction. Adult offspring exposed to maternal high-fructose intake during pregnancy and lactation presented with heavier body weights, fattier livers, and broader areas under the curve in glucose tolerance test values than control offspring. Serum levels of alanine aminotransferase, aspartate aminotransferase, glucose, triglycerides, and total cholesterol and systolic blood pressure in the maternal high-fructose group were higher than that in controls. However, there were no significant differences in mRNA expressions of renin-angiotensin-aldosterone system genes and sodium transporter genes. These results suggest that maternal high-fructose intake during pregnancy and lactation induces metabolic syndrome with hyperglycemia, hypertension, and dyslipidemia in adult offspring.